An in vitro study of the origanum minutiflorum O. Schwarz & P. H. Davis and Coriandrum sativum L. essential oils as chronic tonsillitis therapeutics: antibacterial, antibiofilm, antioxidant, and cytotoxic activities. Issue 6 (2nd November 2022) - Kostić, Marina; Ivanov, Marija; Markovic, Tatjana; Sanković Babić, Snežana; Barros, Lillian; Calhelha, Ricardo; Sokovic, Marina; Ciric, Ana
ABSTRACT: The chemical composition and biological activity of essential oils (EOs) from leaves of Origanum minutiflorum O. Schwarz & P.H.Davis, and seeds of Coriandrum sativum L. were investigated. Chemical analyses of EOs were performed and the major components were carvacrol (81.5%) and linalool (69.6%), respectively. The antimicrobial activity was assessed against several bacteria originating from the tonsillar tissue. Activities of EOs against Staphylococcus aureus biofilm were investigated, as well as the effect of the mixture of these EOs and antibiotics against the pathogen. The antioxidant activity of both EOs was determined by TBARS assay, and examined wild oregano EO showed better activity. Also, cytotoxicity of EOs was evaluated in vitro and both EOs showed potential to inhibit further proliferation of tumor cells. This study reported for the first time the effects of EOs on chronic tonsillitis causative pathogens, supporting their role as a natural bioactive therapeutic agent with possible antimicrobial applications.